Mathematical modeling of the technological processes of catering products production. (11th December 2019) - Dayong, Nie; Mikhaylov, Alexey; Bratanovsky, Sergey; Shaikh, Zaffar Ahmed; Stepanova, Diana
Abstract: Technological processes of catering products manufacture need energy optimization. This article proposes the improvement of mathematical modeling apparatus at the stage of technological processes design and reconstruction. The authors used data from large restaurant‐type catering enterprises typical for million‐plus cities, some of which prepare fast‐food dishes. The possibilities of calorie generation during photosynthesis and the generation of electricity by photocells were examined to understand the energy benefits for catering enterprises. Emphasis is placed on minimizing energy consumption for heating and cooling in food production cycles using cogeneration, regeneration, and generation from local renewable energy sources. Cooking and storage chambers can be differentiated by thermal potentials. The modeling algorithm is deepened by the introduction of links between power consumption and generation equipment. A set of organizational measures of reconstruction is proposed in the design of production systems, which allows one to save up to 33–80% of the total energy costs of a real network of catering outlets. Practical Applications: The use of modern energy technologies in the production processes of public catering enterprises will reduce total costs by up to 80% and improve the overall environmental friendliness of the food industry. While planning reconstruction of basic energy equipment, buildings, and mechanisms, the following must be taken into account. These include concepts of a healthy diet, local renewable energy resources, cultivating local natural food ingredients, and utilizing heat and calorie emissions. Up to 50% of the existing equipment requires such a reconstruction in public catering in developing countries. The principles recommended by the authors for the reconstruction of the production processes of public catering enterprises require the use of advanced algorithms for the mathematical optimization of energy flows and balances.